Samadhis and memorials at Walkeshwar - Ghosh, Ayan (2023)
The Banganga tank precincts are full of shrines and memorials of those who attained samadhi (state of meditative consciousness) and were buried, instead of cremated. The Dasmaniya Akhada burial ground has been in use since the 18th century as a cemetery for sanyasis of the Goswami community, who attained samadhi here.